A Reflection on my Experiences Engaging Teachers in Professional Development on the Integration of Technology Into their Practice - Fullerton, Tom (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
This piece is an autobiographical reflection on practice. Models of professional development are reviewed based on personal experience in the field working with practicing teachers in a variety of capacities. A case is made for teacher inquiry as a model for sustained professional improvement over time that is personally meaningful and potentially transformative. The reader is invited to consider how education technology leaders can leverage the potential of connected classrooms by transforming teacher practice.